New competencies for the 21st century dental public health specialist. (September 2016) - Altman, Donald; Mascarenhas, Ana Karina
Abstract: The American Board of Dental Public Health (ABDPH) currently recognizes 10 core competencies, which identify the skills, knowledge and understanding expected of all dental public health specialists. The last update to the competencies was 1998. The American Board of Dental Public Health, along with the American Association of Public Health Dentistry and its many partners, initiated a process to revise the competencies. This report presents the process and the new competencies for the dental public health specialist of the 21 st century. Each of the developed competencies is supported by a "statement of intent". These competencies take effect immediately. The new competencies will be used in testing candidates for specialty status beginning with the 2018 ABDPH examination.